Some New Wilker-Type Inequalities for Circular and Hyperbolic Functions - Ling Zhu (Abstract and Applied Analysis)
In this paper, we give some new Wilker-type inequalities for circular and hyperbolic functions in exponential form by using generalizations of Cusa-Huygens inequality and Cusa-Huygens-type inequality.